Attitudes of elderly Austrians towards new technologies: Communication and entertainment versus health and support use - Nicole Halmdienst; Michael Radhuber; Rudolf Winter-Ebmer (Johannes Kepler University Linz, Christian Doppler Laboratory Aging, Health and the Labor Market, 2018)
We use a representative survey from Austria to investigate attitudes towards new technologies in information and communication technology (ICT). The technologies can significantly facilitate the daily lives of an aging population. Our main results indicate that strong gender differences in attitudes towards new technologies exist: men value communication and entertainment devices more, whereas women's attitudes are more positive towards devices that include a specific health or support value. Furthermore, while older cohorts value entertainment devices less than younger ones, no such pattern exists for health and support systems.
Keywords: 330